Apocalyptic Visions - Beyond Corporeality - Pearson, Ann (The journal of religion and film, 1998)
In a world where technology has become the center of the universe, traditional religious teachings regarding the creation or manipulation of human life are at risk. Science and technology challenge and appropriate the divine prerogative to create life, even human life as we know it. In a course called, "The Film Experience", I use two films to raise a variety of issues about the creation and manipulation of life. Although this is not a course on religion and film, two of the movies I use are especially good at raising questions about science, religion, and both the creation and manipulation of human life. Will science bring an end to human life as we know it? Is this result of science and technology good or evil?